No transfer of 3d-multiple object tracking training on game performance in soccer: a follow-up study - Romeas, T.; Goujat, M.; Faubert, J.; Labbé, D. (Psychology of Sport and Exercise, 2025)
The impact of domain-general cognitive `brain` training on improving sports performance is highly debated. This study sought to follow-up on research that showcased the benefits of perceptual-cognitive 3D-Multiple Object Tracking (3D-MOT) training in enhancing the on-field performance of soccer players. Additionally, it explored the correlation between athletes` cognitive performance and early career success.